Synthesis, Type II diabetes inhibitory activity, antimicrobial evaluation, and docking studies of N'-arylidene-2-((7-methylbenzo[4,5]thiazolo[2,3-c] [1,2,4]triazol-3-yl)thio)acetohydrazides - Mor, Satbir; Sindhu, Suchita; Khatri, Mohini; Punia, Ravinder; Jakhar, Komal (European Journal of Chemistry, 2022)
N'-Arylidene-2-((7-methylbenzo[4, 5]thiazolo[2,3-c][1, 2, 4]triazol-3-yl)thio)acetohydrazides (6a-j) were prepared by condensation of 2-((7-methylbenzo[4,5]thiazolo[2,3-c][1,2,4] triazol-3-yl)thio)acetohydrazide with appropriately substituted benzaldehydes in dry methanol and a catalytic amount of glacial acetic acid. The prepared compounds tested for in vitro Type II diabetes inhibition and antimicrobial (antibacterial and antifungal) activities employing α-amylase inhibition assay and the serial dilution method, respectively. Type II diabetes inhibitory assay results of all the tested derivatives revealed that precursor 3 (IC50 = 0.16 μM) and acetohydrazide 6i (IC50 = 0.38 μM) showed comparable activity with standard drug acarbose (IC50 = 0.15 μM). The derivatives 6i against B. subtilis and E. coli with MIC values of 0.0300 μmol/mL, compound 6c against S. aureus (MIC = 0.0312 μmol/mL) and compound 6e against P. aeruginosa (MIC = 0.0316 μmol/mL) exhibited remarkable antibacterial activity, however, compound 6b was found to be more active against the fungal strain C. albicans with MIC value of 0.0135 μmol/mL. All acetohydrazides (6a-j) showed greater potency against all strains tested than their precursors 1-4, which is also supported by the results of molecular docking analysis. Furthermore, no general trend for structure activity relationships was established for Type II diabetes inhibitory activity, nor antimicrobial activities of the tested hydrazones (6a-j).